Molecular Cloning of the Porcine Insulin cDNA Using a Monolayer Culture of Pancreatic Endocrine Cells - Mariko Tsuchiya; Ken Tsuchiya; Hisako Ohgawara (Cell Transplantation, 2001)
Porcine pancreatic endocrine cells are an attractive candidate for islet cell transplantation in view of the immunological properties and structural similarities of porcine insulin to human insulin. We recently established a method of isolation and a primary monolayer culture of porcine pancreatic endocrine cells. In this study, cloning of the porcine insulin cDNA was performed to clarify the genetic background of the purified isolated cells. A homology-based PCR cloning method was employed to determine the sequence using mRNA extracted from the monolayer-forming cells, and the candidate products were then determined by a homology search on the human insulin cDNA. According to the newly identified sequence, rapid amplification of cDNA ends was applied to the 5′ and 3′ ends, and the entire cDNA sequence was determined. Gene and protein expression was confirmed by Northern blotting, immunohistochemistry, and enzyme assay. To examine the transcriptional level, the cultured cells were incubated in a 20 mM D-glucose medium in the presence or absence of 5 μM forskolin. The porcine insulin cDNA exhibited a high homology to the human cDNA and showed 85% matching with the human amino acid sequence. D-Glucose at 20 mM stimulated the insulin secretion and mRNA expression, and further addition of 5 μM forskolin with the glucose was applied as the strongest stimulus in this culture system.